The role of parental mediation strategies and online behaviour on internet addiction in young Indonesian children: a parent survey study. - Theopilus, Yansen; Al Mahmud, Abdullah; Davis, Hilary; Octavia, Johanna Renny (Behaviour & Information Technology, 2026)
Increasing children's access to the internet raises concerns about the internet addiction phenomenon that can adversely impact health and well-being. Children are particularly vulnerable to this problem due to individual limitations and environmental influences, especially from parents. This study investigates parental perspectives on the extent to which parental mediation and children's online behaviour across multiple internet-enabled devices influence internet addiction in children. We recruited 1627 parents of Indonesian children aged 7–11 years old to complete self-administered questionnaires assessing parental mediation, children's online behaviour, and their internet addiction risk. Using the partial least squares-structural equation modelling (PLS-SEM), we tested a model representing the constructs (R2 = 0.529). Our study discovered significant negative predictors of internet addiction, including online activities for learning or productivity (β = −0.068) and five parental mediation strategies: active (β = −0.119), co-use (β = −0.060), restrictive-general (β = −0.216), restrictive-specific (β = −0.150), and supervision (β = −0.181). Two variables were significant positive predictors of internet addiction, including mobile device use (β = 0.284) and recreational online activities (β = 0.157). Both variables also partially mediated the relationship between parental mediation and internet addiction. The findings highlight that the appropriate parental mediation to prevent excessive recreational screen time and encourage positive online activities can be an effective effort to prevent internet addiction in children.